Mechanical properties of biopolymer films - Puaud, Max (2000)
Hard gelatin capsules have been used for drug delivery for a long time. The current production process takes advantage of the very unusual properties of gelatin: gelation, very low viscosity, film mechanical properties and film solubility. Although the hard gelatin capsules present many advantages compared to other drug delivery systems, their uses are restricted because of the animal origin of the gelatin. A HPMC gelling agent system is currently used for producing animal product free hard capsules. This work examines the possibility of using a different system in a similar production process. The gelling conditions of the mixed system, the potential of various film formers and the mechanical properties of some films are considered.